METHODOLOGY, KNOWLEDGE AND ACTIVITY SYSTEM - Shodmonova Zilola Bozorovna (Galaxy International Interdisciplinary Research Journal, 2021)
The article analyzes the systematic study of the research problem through the targeted use of pedagogical research methods, observation, questionnaire, testing, experimental methods and their application in practice.For this, a comprehensive study of pedagogical reality includes objective tasks, taking into account external influences, expected and random influences on research, the study of each pedagogical evidence of reality, for example, repeatedly using various methods, analysis of philosophical, logical and psychological-pedagogical. analysis of research results.